Z generációs hallgatók felsőoktatási motivációjának vizsgálata - Juhász, Csilla (Közép-Európai Közlemények, 2017)
The aim of this essay is to reveal studying motivations of university students among Z generation. The sample includes students of correspondence and full time trainings at the University of Debrecen Faculty of Economics and Business. I have repeated the survey of Gergely and Nagy, but I have studied the members of Z generation. The number of the elements of my sample was 300. The students were asked to evaluate certain personal competences in one part of the survey. When revealing the studying motivations, influences by the family and friends, the tendentiousness, realizing the would-be financial independence, experiencing university memories and improving moral existence were examined. Last but not least I found that the results were nearly the same as Gergely’s findings. In my opinion is that studying motivators came from financial possibilities are important. There are no determining differences in studying motivation between Y and Z generations.